(untitled) (Research, Society and Development, 2021)
Chronic Obstructive Pulmonary Disease (COPD) is considered a set of respiratory diseases such as chronic bronchitis and pulmonary emphysema that are mainly characterized by progressive inflammation and reduced airflow in the airways. It developed mainly from active or passive smoking, inhalation of toxic gases or particles. Its treatment consists of reducing symptoms, progression and improving the lives of its patients. However, this treatment is limited and has side effects with prolonged use, which triggers the need to search for new therapies. The use of medicinal plants in the treatment of lung diseases is growing every day and is proving to be a viable and effective option. Its use is possible due to the presence of secondary metabolites, which have pharmacological activities such as anti-inflammatory and antioxidant. The objective of this work was to carry out a literature review of medicinal plants and active compounds used as a form of treatment for COPD from January 2010 to September 2020. 79 articles were identified, among them the researches involved medicinal plants, compounds isolated from medicinal plants and herbal medicines used in traditional Chinese medicine. In general, the research showed that the identified secondary metabolites showed anti-inflammatory and antioxidant activity that mostly belong to the class of flavonoids, alkaloids, saponins, coumarins and terpenes.